Implementation of Schnorr Digital Signature into Blom’s Key predistribution scheme / Nur Addamera Afieqa Mohd Azri, Fatimah Azzahraa Abdul Ghani and Nur Amni Natasya Roslan - Mohd Azri, Nur Addamera Afieqa; Abdul Ghani, Fatimah Azzahraa; Roslan, Nur Amni Natasya (2023)
In symmetric cryptography, the encryption and decryption processes each employ a different key. There is a problem with the important transaction that has come up that might be expensive and interrupted by an unauthorised person. Therefore, a key pre-distribution scheme is created in order to overcome the mentioned issue. Blom's key pre-distribution scheme is one of the protocols. Blom's key predistribution scheme, uses an integer finite field, making it easy for attackers and criminal activists to intervene. Hence, this study suggests implementing the Schnorr Digital Signature to enhance the security of the original Blom’s. In this proposed method, points generated through the Schnorr Digital Signature will be designed as public identifiers to be used in the original scheme. Each user's private key and session key are generated using the addition of law mathematical process with allocated public identifiers. A shared session key will be obtained by nth users who intend to communicate with each other. As a result, this study will present the overall process of the modification of Blom’s key predistribution scheme. Furthermore, it has been proved that the modified scheme can generate a common session key share between three users such as KAB = KBA = KBC to be used in the encryption and decryption processes. In the future, this method can be improved by using the signing and encryption method also known as signcryption that was proposed by (Zheng, 1997). This method can be used for secure and authenticated message delivery which fulfills both the functions of digital signature and encryption with a cost significantly lower and less in computation time.